Simulations of spatially evolving turbulent boundary layers up to Reθ=4300 - Schlatter, Philipp; Li, Qiang; Brethouwer, Geert; Johansson, Arne V.; Henningson, Dan S. (International Journal of Heat and Fluid Flow, 2010)
A well-resolved large-eddy simulation (LES) of a spatially developing turbulent boundary layer under zero-pressure-gradient up to comparably high Reynolds numbers (Reθ=4300) is performed. The laminar inflow is located at Reδ*=450(Reθ≈180), a position where natural transition to turbulence can be expected. The simulation is validated and compared extensively to both numerical data sets, i.e. a recent spatial direct numerical simulation (DNS) up to Reθ=2500 (Schlatter et al., 2009) and available experimental measurements, e.g. the ones obtained by Österlund (1999). The goal is to provide the research community with reliable numerical data for high Reynolds-number wall-bounded turbulence, which can in turn be employed for further model development and validation, but also to contribute to the characterisation and understanding of various aspects of wall turbulence.The results obtained via LES show that good agreement with DNS data at lower Reynolds numbers and experimental data can be obtained for both mean and fluctuating quantities. In addition, turbulence spectra characterising large-scale organisation in the flow have been computed and compared to literature results with good agreement. In particular, the near-wall streaks scaling in inner units and the outer layer large-scale structures can clearly be identified in both spanwise and temporal spectra. © 2010 Elsevier Inc.
CRIS-Team Scopus Importer:2023-03-21
Keywords: High Reynolds number; Large-eddy simulation (LES); Turbulent boundary layers